COLISTIN RESISTANCE IN CARBAPENEM-RESISTANT KLEBSIELLA PNEUMONIAE STRAINS - Bhaskar, Beena Hosdurg; Mulki, Shalini Shenoy; Joshi, Sangeeta; Adhikari, Ranjeeta; Venkatesh, Bhavana Malavalli (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: There is an increasing use of colistin consequent to increase in the infections caused by carbapenem-resistant Klebsiella pneumoniae.The present study was conducted to determine the minimum inhibitory concentration (MIC) of colistin and the resistance pattern of colistin in carbapenem-resistant K. pneumoniae (CRKP) strains in our intensive care unit (ICU). Methods: Antibiotic susceptibility testing for other antimicrobial agents was done by Kirby-Bauer disk diffusion method. MIC of colistin was determined by agar dilution method. The results of antibiotic susceptibility testing were interpreted as per Clinical Laboratory Standard Institute guidelines 2016 and MIC of colistin were interpreted as per European Committee on Antimicrobial susceptibility testing. The carbapenem resistance was phenotypically detected by modified hodge test and imipenem/imipenem ethylenediaminetetraacetic acid disk method. Results: Out of 518 K. pneumoniae, 329 were resistant to carbapenems, and 91 isolates showed resistance to colistin. The MIC of colistin ranged between 4 and >512 ug/ml and MIC90 was 16 ug/L and MIC50 was 4 ug/ml. A majority of the colistin-resistant isolates were found in multidisciplinary ICU (85/91). Conclusion: The emergence of colistin-resistant strains is a major problem due to limited treatment options for infections caused by CRKP carbapenemase producing K. pneumoniae. Colistin should not be used alone, combination therapy should be preferred.